Smartphone on the Desk: A Study of the Characteristics of Cyberloughing among Schoolchildren and Students - N.V. Sivrikova; T.G. Tatiana; A.E. Perebeinos (Moscow State University of Psychology and Education, 2023)
This study aims to research a new form of students' deviation: cyberloafing. This term refers to the use of Internet technologies during classes for non-educational purposes. Children get distracted during lessons by online or off-line activities. A sample of the study consists of students and schoolchildren from Chelyabinsk city. The study involved 233 people aged 13 to 20 years. 146 schoolchildren aged 13–15 years (42% boys and 58% girls) and 87 students aged 17–20 (40% male and 60% female) were recruited for this study. We use the cyberloafing scale proposed by Y. Akbulut (in the Russian version by N.V. Sivrikova). The results of the research demonstrate that the level of cyberloafing is quite low and correlates with participants' gender and educational level. Differences between schoolchildren and students correspond to the structure of cyberlоafing behavior.